Development of Nanoemulsions Containing Essential Oils for Gel Formulations - Naewkanya, Pattama; Daothaisong, Pemika; Sowasod, Nataporn; Loruthai, Orathai; Bunwatcharaphansakun, Phichaporn; Tanthapanichakoon, Wiwut (Applied Science and Engineering Progress, 2026)
The formulations of nanoemulsions containing lime-peel essential oils (LPO) and LPO-encapsulated nanoemulsion gels (nanoemulgels) for a cosmetic product were investigated. The IC50 value for LPO essential oils, which was determined using the 1, 1-Diphenyl-2-picrylhydrazyl (DPPH) method to determine the antioxidant activity of the oils, is 21.7 ± 0.5 mg/ml. To facilitate the preparation of the nanoemulsion formula and ensure that the essential oils were in the form of oil-in-water (O/W) nanoemulsions, the most suitable surfactant, and cosurfactant utilized were Brij IC20 and glycerine, respectively. When LPO (concentration of 3% by weight) and the surfactant and cosurfactant (total concentration of 20% by weight) were mixed at a weight ratio of 3:1, the resulting LPO nanoemulsion contained fine particles with a uniform particle size distribution, low zeta potential, and good physical stability. All results exhibited that nanoemulsions stabilized by a mixture of Brij IC20 and glycerine are suitable as delivery vehicles for LPO. Nanoemulgel was also manufactured utilizing the nanoemulsion. The optimal gelling agent for the nanoemulgel was determined to be Carbopol 940 with a concentration of 0.3 % by weight. The nanoemulgel was physically stable with a pH of 5.3 (near the skin pH) and an adequate viscosity of 1290 cP.